Targeting DLL4 in tumors shows preclinical activity but potentially significant toxicity. - Li, J; Jubb, A; Harris, A (2010)
Evaluation of: Yan M, Callahan CA, Beyer JC et al.: Chronic DLL4 blockade induces vascular neoplasms. Nature 463, E6-E7 (2010). Delta-like ligand 4 (DLL4) is a Notch ligand that is critical in the formation of a functional vascular network in tumors. Blockade of DLL4-mediated Notch signaling strikingly increases nonproductive angiogenesis, but significantly inhibits tumor growth in preclinical mouse models. Thus, DLL4 has emerged as an attractive target for cancer therapy. Anti-DLL4 antibodies have recently entered clinical trials. However, the potential toxic effects of anti-DLL4 are poorly understood. In this article, Yan et al. reported that chronic DLL4 blockade abnormally activates endothelial cells, causes pathological changes of multiple organs and induces vascular neoplasms. The findings need confirmation in further studies using different tumor-bearing animals but, nevertheless, raise important safety concerns regarding the use of anti-DLL4 agents and warrant monitoring for these effects in clinical trials for targeting DLL4.